The effect of increasing the general budget of the state on change in the inflation rate the Syrian pound - قوشجي إبراهيم; عصام إسماعيل (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aims to study the impact of the increase rate of the general budget of the state on the changes in the inflation rate using correlation and regression analysis to determine the effect of changes in public expenditures, which represent the total government spending (investment and consumption), including the implementation of development and service plans, on the Syrian pound’s inflation rate. The study employed a simple linear regression analysis to explore the relationship between these two variables. The study concluded that the rate of increase in public expenditures did not have an impact on the change in the Syrian pound’s inflation rate, indicating that the general budget of the state has lost its primary role in the national economy.